2019
DOI: 10.1186/s12885-019-5658-5
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a rat ovarian peritoneal metastasis model to study pressurized intraperitoneal aerosol chemotherapy (PIPAC)

Abstract: Background pressurized intraperitoneal aerosol chemotherapy (PIPAC), with or without electrostatic precipitation (ePIPAC), was recently introduced in the treatment of peritoneal metastases (PM) from ovarian cancer (OC). Preliminary clinical data are promising, but several methodological issues as well the anticancer efficacy of PIPAC remain unaddressed. Here, we propose a rat ePIPAC model that allows to study these issues in a clinically relevant, reproducible, and high throughput model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…In addition, we identified the optimum time frame within which distribution of intraperitoneal compounds reached their optimum. Of note, we found that PIPAC had the best distribution pattern among the three different forms of IPC studies, which is consistent with data found in the rat model [ 13 ] and in humans [ 20 ]. This suggests that our mouse model is an adequate surrogate for studying human IPC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, we identified the optimum time frame within which distribution of intraperitoneal compounds reached their optimum. Of note, we found that PIPAC had the best distribution pattern among the three different forms of IPC studies, which is consistent with data found in the rat model [ 13 ] and in humans [ 20 ]. This suggests that our mouse model is an adequate surrogate for studying human IPC.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, animal models allowing for rapid, reproducible, and inexpensive study of different forms of IPC are warranted. Recently, van de Sande et al developed an animal model of IPC using Wistar rats undergoing laparoscopy with capnoperitoneum, aerosolized chemotherapy, and electroprecipitation [ 13 ]. This tumor model used a xenograft of ovarian PM based on SKOV-3 luciferase-positive cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the feasibility and added benefits of the PIPAC therapy with nanoparticles still largely remain to be elucidated. In this study, we explored the in vivo potency of cisplatin-loaded pARG-HA NPs in a rat model of intraperitoneally disseminated human ovarian cancer [56][57] , with a special focus on the potential advantage of formulating cisplatin into a nanoparticle system and whether or not liquid aerosolization is beneficial compared to liquid injection of NPs into the peritoneal cavity. Tumor-bearing rats were dosed either with free cisplatin (5 mg/kg) or cisplatin-loaded pARG-HA NPs (at 5 mg/kg doseequivalent level of Pt) through a single injection or nebulization (PIPAC) (Figure 3A).…”
Section: Aerosolization Of Cis-parg-ha Nps Synergistically Results In a Pronounced Antitumor Efficacy In A Rat Model Of Peritoneal Metastmentioning
confidence: 99%
“…It has also been suggested that adding electrostatic loading and following precipitation of the therapeutic aerosol might optimize tissue effects of PIPAC [22]. This hypothesis was confirmed in an animal model [14,28], and ePIPAC has successfully entered clinical practice [29,30].…”
Section: Discussionmentioning
confidence: 88%